How to disseminate the research results on climate change impacts in cities to guide adaptation public policies ? Application to the Paris region (France) - Julie André; Benjamin Le Roy; Aude Lemonsu; Morgane Colombert; Valéry Masson (Climate Services)
The construction of efficient climate services relies on the interaction between decision-makers and scientists. Urban heat island is an issue that already preoccupies public authorities and is likely to be exacerbated by climate change, making assessment of its evolution crucial for effective urban policymaking and to size adaptation measures. This study analyzed interviews with 13 public stakeholders in the Paris area (France), highlighting their diverse needs for urban climate data. Their feedback on the high-resolution climate projections for the Paris region was assessed to provide recommendations to researchers for the effective dissemination of urban climate data. Public stakeholders in the Paris area need urban climate data for various purposes (awareness, diagnosis, decision support, and evaluation) and thus seek diverse types and formats of information. High-resolution climate projections may meet parts of these needs, but two key points require attention: (i) climate models appear to be difficult to apprehend by public stakeholders, thus an effort of pedagogy is necessary, (ii) climate projections often extend to 2100, but stakeholders primarily need short- to medium-term forecasts that align with public policy timelines. Indicators on extreme impacts and risks are a strong demand of public actors, especially in the health and energy sectors. Additionally, since recent urban climate resources remain largely unseen by public actors, we recommend enhancing its dissemination through local institutes recognized by policymakers, such as urban planning agencies. In summary, this case study provided valuable insights into the key mechanisms required for effectively disseminating climate research to promote climate change adaptation.